If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3n = 4n + -4 Reorder the terms: 3n = -4 + 4n Solving 3n = -4 + 4n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-4n' to each side of the equation. 3n + -4n = -4 + 4n + -4n Combine like terms: 3n + -4n = -1n -1n = -4 + 4n + -4n Combine like terms: 4n + -4n = 0 -1n = -4 + 0 -1n = -4 Divide each side by '-1'. n = 4 Simplifying n = 4
| 8n+3n=-22 | | 2x+26=44 | | 2x+10=x+36 | | 35-14=-35 | | 96+x=40x | | 5x+100=-235 | | -6s=36 | | y=(1-x)/1.2 | | (x+7)(x-2)=(x+1)(x+1) | | 1.4(x+1.2)=7.8 | | -24/5=31/2h | | (x+7)(x+2)=(x+1)(x+1) | | m=z+bx | | 12x+8y+7x=z | | 2(3x-4)+6(x-5)=-3(4-5x)+5x-16 | | 4y-1x+2y=z | | [8+(-4)]-5= | | -8/12-21/12 | | 12+[-5+(-4)]= | | (7/x)-(1/7)=(2/x) | | 3(3x-2)=15 | | 2(3x-5)+6(x-3)=-3(3-5x)+5x-1 | | 2-4(x+3)=4-2(3x+5) | | 2.5=2/s | | -2(-3)-5y=4 | | -2y-42=3(y+1) | | -2/3(6*3-45)-2(3) | | 9x+2x=0x | | 21-u=17 | | 3x^2-4y=7 | | 2/5*15-1=5 | | (6a+1)(5a+2)= |